Prediction of Progressive Failure Behaviour of Composite Skewed Hypar Shells Using Finite Element Method. (15th September 2014) - Ghosh, Arghya; Chakravorty, Dipankar
Abstract : Progressive failure behaviour of laminated composite skewed hypar shells is investigated in this paper through finite element approach. For composite materials which are weak in transverse shear, failure may initiate at any inner lamina or interface and may remain undetected and unattended to. Such latent damages may progress gradually and lead to a sudden total ply failure. An iterative method is adopted using the various failure theories to predict the first ply failure load. After the first ply failure, the stiffness of the failed element is totally discarded from the laminate and the remaining laminate is considered for further analysis. The developed finite element code is validated through solution of a benchmark problem. Numerical experiments are carried out to obtain the first ply and progressive failure of simply supported hypar shells under transverse distributed load. While obtaining the failure loads, the shell is considered to be under plane stress condition and in linear elastic range. Results are studied meticulously to extract a set of conclusions of practical significance regarding the failure characteristics of composite hypar shells.